Bagaimana menjadi orang tua anak dengan cerebral palsy? A parent acceptance - Yubaedi Siron; Veda Ria Perdana; Sri Rahayu Saputri; Dewi Nur Hanifah (Institut Agama Islam Negeri Langsa, 2020)
Parents who have down syndrome children find it challenging to accept the presence in their early stages of life, even though parental acceptance becomes the primary factor of the successful parenting of children with cerebral palsy. This study aims to describe the acceptance of parents who have children with cerebral palsy. This study uses a qualitative approach using the phenomenological method for revealing the phenomenon of parents' compliance with cerebral palsy children. The data collection technique uses structured interviews involving 5 participants. The results of this study indicated that parents are trying to accept the child's condition by being grateful, surrendering, socializing, and sharing information with fellow parents of children with cerebral palsy. Support from the closest relatives and friends is an essential factor that makes the process of acceptance easier for parents to undertake.